Evaluation of Stainless-Steel Mesh 304 Cathode Performance in a Microbial Fuel Cell for Tofu Wastewater Treatment - Satar, Ibdal; Uswatun Khasanah; Titisari Juwitaningtyas; Edy Herianto Majlan; Waled Abdo Ahmed; Byung Hong Kim (Indonesian Journal of Environmental Management and Sustainability, 2025)
Currently, tofu wastewater (TWW) is one of the major environmental issues that must be addressed. When discharged untreated TWW into natural water bodies or soil, it poses a serious threat to the environment. Therefore, effective treatment of TWW is crucial before to disposal. As an advanced bio-electrochemical technology, the microbial fuel cell (MFC) offers a promising approach to reduce pollutants while simultaneously generating electricity. However, the choice of cathode material is crucial for enhancing MFC performance. This study aims to evaluate the performance of an MFC using an SSM-304 cathode with TWW as the target substrate. Several characteristics of TWW including pH, chemical oxygen demand (COD), biological oxygen demand (BOD), total solids (TS), total dissolved solids (TDS), and total suspended solids (TSS), were analyzed before and after MFC treatment. Additionally, the performance of the MFC system was further evaluated based on voltage output (V), current density (J), coulombic efficiency (CE), and MFC efficiency (?MFC). The results show that COD and BOD were reduced by 69.56% and 64.00%, while TS, TDS, and TSS increased by 48.79%, 32.24%, and 45.15%, respectively. The MFC system with SSM-304 produced a voltage of 167 mV, a current density of 267.2 mA/m², a coulombic efficiency of 3.35%, power density of 27.89 mW, and MFC efficiency of 10.43%. Overall, this study demonstrated the potential of MFCs for simultaneous wastewater treatment and energy recovery.